ASPECTOS EPIDEMIOLÓGICOS DA PARACOCCIDIOIDOMICOSE - Vicentini, A.P.; Da Silva, D.F.; Oliveira, L.E.; Zamboni, I.M.; Assis, C.M.; Portela-Lindoso, A.A. (Revista do Instituto Adolfo Lutz, 2002)
Ver PDF.